2021
DOI: 10.1111/clr.13701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings and history of bone loss at implant sites

Abstract: Objectives The aim of the present study was to evaluate whether clinical findings at implant sites are relevant as screening tests for a history of marginal bone loss. Material and Methods 427 patients provided with implant‐supported reconstructions 9 years earlier were evaluated clinically (probing pocket depth (PPD), bleeding on probing (BoP)) and radiographically. A history of bone loss was confirmed through baseline documentation. Diagnostic accuracy was evaluated through receiver operating characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…This is because according to those results, this low sensitivity indicates a high inability to diagnose diseased implants, as truly pathological. Moreover, the validity of the proposed clinical criteria for the diagnosis of peri‐implantitis is also in question, since they also have reported that while blood on probing showed a high level of sensitivity, the sensitivity of probing pocket depth was generally low 32 . But even more, bleeding on probing must be interpreted with caution, as it may originate not only because of a true pathological condition but also as a consequence of trauma upon the own maneuver of probing 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because according to those results, this low sensitivity indicates a high inability to diagnose diseased implants, as truly pathological. Moreover, the validity of the proposed clinical criteria for the diagnosis of peri‐implantitis is also in question, since they also have reported that while blood on probing showed a high level of sensitivity, the sensitivity of probing pocket depth was generally low 32 . But even more, bleeding on probing must be interpreted with caution, as it may originate not only because of a true pathological condition but also as a consequence of trauma upon the own maneuver of probing 33 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the Swedish study series initiated by Derks and colleagues, 20% of measurements were made on panoramic radiographs 10 . Moreover, more recent studies conducted and published by others also use data from panoramic radiographies to analyze MBL around implants 7,32 . It is remarkable that in the most recent consensus, 2,73 “intraoral radiographies” are not required specifically, surely due to the important limitations of the intraoral radiographies described above.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of the present study include the absence of a control group and the retrospective design of the study and the lack of longitudinal assessment of interproximal radiographic bone level, due to the strict compliance with the current national legislation. As clinical parameters (BOP and PD) can be considered predictors of disease progression (Berglundh et al, 2021; Carcuac et al, 2017; Karlsson et al, 2019), the sole presence of BOP+ in absence of PD values ≥6 mm was not considered sufficient for taking x‐rays. Indeed, in these circumstances the therapeutic approach would have been in the first place non‐surgical no matter what.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has some limitations mainly related with the nature of the available literature. Several factors such as implant surface characteristics, 63 configuration of peri-implant defect, 64, 65 frequency and quality of supportive therapy 8, 66 can affect the results of surgical treatment of peri-implantitis, but none of these factors could be considered in the present meta-analyses. Furthermore, 6-month follow-up in some of the included RCTs may be too short for detection of significant effect on MBL changes and may not account for the relatively high incidence of disease recurrence following surgical therapy of peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%